Impact of IFRS 15 adoption on performance measurement in healthcare – the case of National Health Service Foundation Trusts - Anita Tenzer (Cogent Business & Management, 2024)
The International Financial Reporting Standard (IFRS) 15, `Revenue from Contracts with Customers', became effective for National Health Service (NHS) bodies from the annual period beginning 1 April 2018. NHS Foundation Trusts, as part of UK public sector organisations, adopted IFRS for their 2009/2010 financial statements to improve the consistency and comparability of financial reports globally and to follow best practices from the private sector. The implementation of new or revised accounting standards can have both intended and unintended effects. Understanding these effects is essential for healthcare policymakers and managers to navigate the changes this standard brings. This study analyses the impact of IFRS 15 on the financial performance of University and Teaching Hospitals Foundation Trusts, considering both financial and management accounting perspectives. The research initially outlines the expected effects of the new revenue recognition standard. It then addresses unique considerations within the healthcare sector before empirically evaluating the significance of annual financial performance changes after IFRS 15 implementation, specifically in terms of accounting effects. This exploration paves the way for discussions on further anticipated effects. The article uses Friedman's test to analyse the impact of IFRS 15 on total operating income for a sample of 33 University and Teaching Hospitals Foundation Trusts and finds that the adoption of the new revenue recognition standard had a significant impact on this item, i.e. financial performance was affected, which is classified as an unintended effect.
Keywords: I18; M40; M48; 650; IFRS 15; NHS Foundation Trusts; performance measurement; financial accounting; management accounting; earnings management; hospitals